An epidemiological study to assess prevalence and behavior related to substance abuse among urban Bikaner population Rajasthan - Qureshi, Asif Ahmed; Acharya, Rekha; Sharma, Gaurav; Sethia, Renu; Shekhawat, Kirti; Kawatra, Abhishek (International Journal Of Community Medicine And Public Health, 2017)
Background: Substance abuse exists in the world since time immortal; it has become a serious global problem in recent times. Methods: This was a cross sectional community based study performed from March 2016 to August 2016 among resident of UHTC Mukta Prasad dispensary (urban health and training center) attached to Sardar Patel Medical College, Bikaner. Results: Overall prevalence was 25.14%. Majority of people were using only tobacco (67.07%) while 20.12% people were consuming tobacco and alcohol both, only alcohol was used by 10.98% people and rest (1.83%) were having other types of substances like Doda-post etc. Conclusions: Almost 1/4th of study population was abusing one or the other substance. Most commonly abused substances were tobacco and tobacco+alcohol.